Performance and carcass characteristics of lambs ½ Dorper + ½ Santa Inês, slaughtered with different thicknesses of subcutaneous fat - Nascimento,Urias Fagner Santos (2018)
SUMMARY The aim of this study was to evaluate the effect of subcutaneous fat thickness (SFT) on slaughter in lambs ½ Dorper + ½ Santa Inês (DSI) on performance, carcass characteristics and commercial cuts. It was used twenty-four lambs, slaughtered with 2mm, 3mm and 4mm SFT. There was an effect of SFT on performance: for days of confinement (2mm = 51.38, 3mm = 66.50, 4mm = 91.63 days), age at slaughter (2mm = 139.38, 3mm = 159.88, 4mm = 171.00 days), final body weight (2mm = 33.50, 3mm = 42.81, 4mm = 46.19 kg), total weight gain (2mm = 18.75, 3mm = 25.08, 4mm = (2mm = 0.44, 3mm = 0.39, 4mm = 0.28kg), slaughter weight (2mm = 32.76, 3mm = 39.79, 4mm = 44.88 kg), body condition score (2mm = 2.97, 3mm = 3.13, 4mm = 3.56); for carcass characteristics: warm carcass weight (2mm = 15.33, 3mm = 19.16, 4mm = 21.90 kg) and cold (2mm = 15.03, 3mm = 18.75, 4mm = 21.47), cooling losses (2mm = 0.00234; 3mm = 0.00333; 4mm = 0.00201 kg), carcass yields: in the refrigerator (2mm=46,79; 3mm=48,30; 4mm=48,79%); commercial (2mm = 45.88, 3mm = 47.25, 4mm = 47.82%) and true (2mm = 52.93, 3mm = 54.51, 4mm = 55.67%); carcass compactness index (2mm= 0,250; 3mm=0,30; 4mm=0,33 kg/cm) for cut weights; neck (2mm=0,44; 3mm=0,55; 4mm=0,56 kg); palette (2mm=1,38; 3mm=1,61; 4mm=2,14 kg), flank steak (2mm=2,16; 3mm=2,73; 4mm=3,19 kg), loin (2mm=0,93; 3mm=1,14; 4mm=1,25 kg), and leg (2mm=2,68; 3mm=3,20, 4mm=3,76 kg). For the tissue composition of only the muscular cuts of the neck (2mm = 50.24, 3mm = 51.44, 4mm = 55.34%), bone of the neck (2mm = 30.24, 3mm = 29.63, 4mm = 25.91%), of the loin (2mm=15,05; 3mm=24,63; 4mm=24,71%) and the leg (2mm=11,38; 3mm=13,33; 4mm=13,13%), they presented differences between the SFT (p> 0.05). It is recommended to slaughter lambs ½ Dorper + ½ Santa Inês with 3mm of SFT.